Advanced modification of main types of excimer laser resonators - Baschenko, S.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
In the paper proposed are some simple modifications of plane-parallel and unstable telescopic resonators the most widely used in excimer lasers. These can increase output energy, density of emission power and improve the shape of a laser beam cross-section. Physical essence of these modifications lies in formation of an optically closed zone in some part of the resonator, which prevents photons to escape. This yields in their increased concentration (the so-called `photon concentrator') that favors discharge stabilization and shifting this zone towards a cathode where main instabilities of an electric discharge originate. In the plane-parallel cavity such a photon concentrator can be realized by application of an output window with a mirror area in the range corresponding to the cathode space. Using the scheme in our conditions we observed the increase of laser pulses emission energy by 15% and, respectively, their energy density by 44% with simultaneous decreasing the laser beam shape extent (in its cross-section) and proportional reducing a beam divergency along the diminished size. In the unstable telescopic resonator this kind of a closed zone (photon concentrator) should exist by definition and, as a rule, in a paraxial part of it. The modification proposed consists in shifting this zone towards a cathode. In our conditions this way provided the increase of laser pulse emission energy by 5% with simultaneous improvement of the laser beam shape (in its cross-section). It means shifting a shaded spot towards a border of the beam cross-section and, in such way, to its practical removal out of operating beam.